The house in Scarsdale : a memoir for the stage - O'Brien, Dan (Playwright) (Oberon modern plays., 2019)
Winner of the 2018 PEN America Award in Drama As Tolstoy said, 'All happy families are alike; each unhappy family is unhappy in its own way.' In The House in Scarsdale, playwright Dan O'Brien traces the roots of his family's particular unhappiness to learn why his parents and siblings cut him off years ago. The more Dan learns about his family, the more mysterious the circumstances surrounding their estrangement become, until his world is shaken when rumours surface that his real father might be another member of the family. Is his pathological pursuit of the truth worth the risk' Or should he follow the advice of a psychic and make his life a never-finished work of art'